Dual versus single antiplatelet therapy after transcatheter aortic valve replacement: a systematic review and meta-analysis. (3rd October 2022) - Eikelboom, R; Qui, Y; Kim, K; Whitlock, R; Belley-Cote, E
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is the intervention of choice for patients with severe symptomatic aortic stenosis who have high or intermediate surgical risk. TAVR valves are at risk of thrombosis and serious sequelae including stroke, peripheral embolism, and valve dysfunction requiring intervention. The optimal method of antithrombotic therapy to reduce risk of thrombosis with an acceptable increase in risk of bleeding is uncertain. Objectives: This systematic review and meta-analysis assesses the effects of dual antiplatelet therapy (DAPT) versus single antiplatelet therapy (SAPT) on mortality, thrombosis and bleeding in patients undergoing TAVR. Methods: We systematically searched EMBASE, MEDLINE and CENTRAL from January 1, 2002 until February 9, 2021 for randomized trials comparing DAPT to SAPT after TAVR. Two reviewers independently screened titles and abstracts, and then the full text of potentially relevant articles in duplicate. Data abstraction and risk of bias was also performed in duplicate. Risk ratios and 95% confidence intervals were pooled using the Mantel-Haenzel method and random effects modelling. We assessed the certainty of the evidence for each outcome using the Grading of Recommendations, Assessments, Development and Evaluation (GRADE) approach. Results: We included 4 randomized controlled trials of 1086 patients. Risk of bias was low or somewhat concerning for all studies. We found no difference in mortality (risk ratio (RR) 1.02, 95% confidence interval (CI), 0.63 to 1.63) or stroke (RR 1.03, 95% CI 0.57–1.84), but a significant increase in major bleeding (RR 2.04, 95% CI, 1.31–3.19), with DAPT compared to SAPT. There were too few events to conduct meta-analysis for clinical valve thrombosis, subclinical valve thrombosis, transvalvular gradients on echocardiography, or aortic valve reintervention. The certainty of the evidence was low or very low due to risk of bias, inconsistency, and imprecision. Conclusions: There is very low certainty evidence that DAPT has little to no effect compared to SAPT on mortality and stroke. There is low certainty evidence that DAPT likely causes more major bleeding than SAPT. Funding Acknowledgement: Type of funding sources: None.